2023
DOI: 10.1097/prs.0000000000010188
|View full text |Cite
|
Sign up to set email alerts
|

Extended Duration Venous Thromboembolism Chemoprophylaxis Following Microsurgical Breast Reconstruction: Analysis of Trends in Postoperative Anticoagulation

Abstract: Background: Microsurgical breast reconstruction following mastectomy represents a high-risk patient group for venous thromboembolism (VTE), but there is limited consensus on postoperative prophylaxis duration. The aim of this study was to characterize the risk of VTE after microsurgical breast reconstruction, the risk reduction associated with postoperative outpatient VTE prophylaxis, the clinical factors associated with VTE events, and surgeon prescribing patterns regarding outpatient VTE prophylaxis. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A recent study reported VTE rates of 0% in those discharged on VTE prophylaxis and 1.8% in those who were not discharged on prophylaxis. 25 Whereas the incidences appear similar, it is possible that our higher incidence of VTE for patients who received postoperative anticoagulation within the first 30 days (2.6%) captures patients who received prophylactic anticoagulation during their hospitalization but not after discharge, as our study did not distinguish between hospitalization and discharge medications.…”
Section: Incidence Of Postoperative Vte After Autologous Breast Recon...mentioning
confidence: 71%
See 2 more Smart Citations
“…A recent study reported VTE rates of 0% in those discharged on VTE prophylaxis and 1.8% in those who were not discharged on prophylaxis. 25 Whereas the incidences appear similar, it is possible that our higher incidence of VTE for patients who received postoperative anticoagulation within the first 30 days (2.6%) captures patients who received prophylactic anticoagulation during their hospitalization but not after discharge, as our study did not distinguish between hospitalization and discharge medications.…”
Section: Incidence Of Postoperative Vte After Autologous Breast Recon...mentioning
confidence: 71%
“…Although there are trends toward routine use of VTE thromboprophylaxis among breast reconstruction surgeons, our study found that more than 50% of patients did not receive anticoagulation postoperatively. 10,19 In the retrospective study by Le et al, 25 98.4% of 22,505 patients were discharged without VTE prophylaxis. Our analysis of 8221 patients demonstrated that heparin and enoxaparin are effective in reducing the rates of postoperative VTE, consistent with the findings of Le et al, 25 who found that 0 of 356 patients on postoperative VTE prophylaxis developed VTE in the first 90 days postoperatively.…”
Section: Incidence Of Postoperative Vte After Autologous Breast Recon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Breast reconstruction patients face an elevated baseline risk of VTE due to underlying malignancy, prolonged procedure times, and the necessity for postoperative hospitalization, with incidence reported between 0.13% to 6% amongst various studies. [24][25][26][27] Previous studies further identified increased DVT risks with immediate reconstruction, obesity, a history of chemotherapy, and chronic pulmonary disease in patients undergoing autologous breast reconstruction. 28,29 As such, in addition to the use of chemoprophylaxis and other nonpharmacological interventions for DVT prevention, some authors had further recommended an extended course of oral anticoagulant post-discharge to mitigate this risk, 30,31 although this was not part of our institutional practice.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…I n this issue, Le et al sought to characterize the risk of venous thromboembolism (VTE) after microsurgical breast reconstruction, the risk reduction associated with postoperative outpatient VTE prophylaxis, and surgeon prescribing patterns regarding outpatient VTE chemoprophylaxis. 1 This is an important topic because women who undergo autologous microsurgical breast reconstruction following mastectomy are at an increased risk for postoperative VTE, yet evidencebased guidance for VTE chemoprophylaxis after discharge has lagged behind other surgical and medical subspecialties. 2 Although the optimal duration, type, and dosing for chemoprophylaxis remain unknown for this population, there is a growing consensus that chemoprophylaxis limited to the inpatient stay is inadequate.…”
mentioning
confidence: 99%